The Purification of Islam by Anregurutta H. Muhammad As’ad in Wajo 1928-1952 AD (Historical Analysis) - Jaya, Muchtar; Dahlan, M.; Santalia, Indo (International Journal of Islamic Studies, 2023)
The aim of this study was to determine the influence of the purification of Islam by Anregurutta H. Muhammad As’ad on the religious attitudes of Wajo citizens. The researchers used a sociological and historical approach. This study is classified as library research; the data was collected by quoting, adapting, and analyzing using content analysis on literature that is representative and has relevance to the problem, then reviewing and concluding it. The results of the study showed that Anregurutta H. Muhammad As’ad’s Islamic purification movement in Wajo has two concepts, namely 1) Islamic education and 2) Islamic da’wah. He applied the concept of Islamic education through Mengaji Tudang as non-formal education and Tahfidz of Al-Qur’an and Madrasah of Arabah Islamiyah (MAI) as formal education. Meanwhile, the concept of Islamic da’wah was applied to the formation of muballigh cadres as a program of non-formal Islamic da’wah and to al-Dzikra Magazine as formal da’wah.